2017
DOI: 10.1186/s12934-017-0707-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of deleted, atoxic atypical recombinant beta2 toxin in a baculovirus system and production of polyclonal and monoclonal antibodies

Abstract: Background Clostridium perfringens is an important animal and human pathogen that can produce more than 16 different major and minor toxins. The beta-2 minor toxin (CPB2), comprising atypical and consensus variants, appears to be involved in both human and animal enterotoxaemia syndrome. The exact role of CPB2 in pathogenesis is poorly investigated, and its mechanism of action at the molecular level is still unknown because of the lack of specific reagents such as monoclonal antibodies against the CPB2 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Instead, CaCo-2 cell damage was observed after the confluent monolayer of cultured cells came into contact with 10 μg/ml of the full-length PLC or a culture supernatant that was diluted up to four times. The data were in accordance with the results obtained for the CPB2 atypical recombinant protein, which was expressed in baculoviruses [24].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Instead, CaCo-2 cell damage was observed after the confluent monolayer of cultured cells came into contact with 10 μg/ml of the full-length PLC or a culture supernatant that was diluted up to four times. The data were in accordance with the results obtained for the CPB2 atypical recombinant protein, which was expressed in baculoviruses [24].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the best results were achieved in terms of production, satisfactory yield, and purity of the rBacCPA250-363H6 protein, when the cellular lysate was subjected to Ni-NTA His-select-affinity chromatography under denaturing conditions. As suggested for other recombinant proteins, such as CPB2 [24], this feature could be explained with respect to the folded protein by the significant exposure of the C-terminal 6xHis tag of the denatured antigen. As shown in Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Direct comparisons between deterministic diffusion tractography and gold-standard tract-tracing methods in rhesus macaques have revealed that diffusion-based connectome reconstructions generally produce reasonable estimates of large white matter projections (Dauguet et al, 2007 ; van den Heuvel et al, 2015 ). However, because tensor-based deterministic tractography approaches yield sparse connectomes (high specificity with comparatively low sensitivity) and higher-order probabilistic tractography approaches yield dense connectomes (high sensitivity with comparatively low specificity), other groups have begun to study tradeoffs between connectome sensitivity and specificity (Zalesky et al, 2016 ). Initial studies in this regard suggest (both empirically and theoretically) that “specificity is at least twice as important as sensitivity when estimating key properties of brain networks, including topological measures of network clustering, network efficiency and network modularity” (Zalesky et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, because tensor-based deterministic tractography approaches yield sparse connectomes (high specificity with comparatively low sensitivity) and higher-order probabilistic tractography approaches yield dense connectomes (high sensitivity with comparatively low specificity), other groups have begun to study tradeoffs between connectome sensitivity and specificity (Zalesky et al, 2016 ). Initial studies in this regard suggest (both empirically and theoretically) that “specificity is at least twice as important as sensitivity when estimating key properties of brain networks, including topological measures of network clustering, network efficiency and network modularity” (Zalesky et al, 2016 ). Therefore, although not perfect, the deterministic, tensor-based tractography approach used to generate our functionally-defined white matter atlases likely errs in the proper direction when it comes to connectome sensitivity vs. specificity tradeoffs.…”
Section: Discussionmentioning
confidence: 99%